La technique et la chair. De l’ensarkosis logou a la critique de la societe technicienne chez Bernard Charbonneau, Jacques Ellul et Ivan Illich - Cérézuelle, Daniel (Mechane, 2020)
It is why man exists as flesh and body that the rising power of technique may subject man’s daily life to given depersonalising constraints. Such an intuition is at the heart of some contemporary critiques of technological society. Since the end of the Thirties, indeed, the concepts of flesh and incarnation, as the very heritage of Judeo-Christian spirituality, represented the fulcrum for a stream of technocritical thought. Accordingly, authors like Bernard Charbonneau, Ivan Illich and Jacque Ellul, challenge the depersonalisation of technique by claiming both the exigency of incarnation and the attention to the very flesh dimension of human existence.